Border (AmeriQuests, 2017)
The first chapter of the novel 'To Patagonia'Just past the Mexican Border two men burn their passports. Under false identities, they make their way south to create new lives. In a time where their only crime is love, running AWOL from pending Don’t Ask Don’t Tell dishonorable discharges, and motivated by the looming expiration of their new documents, they must find a place to settle down and become citizens of a new land, or lose citizenship entirely.On the journey to Patagonia the two men face life-threatening obstacles and must make connections and friendships in the most unlikely of places. Peopled with a ship captain, a stray dog, mountain climbers, explorers, and gauchos, all with the common understanding of life as a refugee, To Patagonia is a tale of hope against hope, where the search for home is a universal journey that all people must walk.